According to the Remainder Theorem, when a polynomial \( f(x) \) is divided by \( x - c \), the remainder of that division is equal to \( f(c) \).
In this case, we are given that when \( f(x) = x^4 - 5x^3 + 8x \) is divided by \( x - 3 \), the remainder is \( -30 \). This means:
\[ f(3) = -30 \]
Now, let's analyze the options given:
- \( f(-3) = -30 \) — This is not supported by the information given.
- \( f(3) = -30 \) — This is correct based on the Remainder Theorem.
- \( f(3) = 30 \) — This is incorrect because we established from the theorem that \( f(3) = -30 \).
- \( f(-3) = 30 \) — This is also not supported by the information given.
Thus, the correct choice according to the Remainder Theorem is:
\[ \boxed{f(3) = -30} \]